Age wise comparative analysis of patients undergoing total knee arthroplasty: a multicenter indigenous experience - Rudraraju, Ravi Teja; Bajwa, Supreet; Aneja, Kunal; Ponnanna, Karineravanda Machaiah (International Journal of Research in Orthopaedics, 2024)
Background: This study assesses the mid-term clinical and functional outcomes, implant survivorship and impact of age on patients implanted with either cruciate retaining/posterior stabilized (CR/PS) total knee system (TKS). Method: This is an ongoing, prospective, multicentre, real-world study enrolling 300 patients: younger adults (<55 years; n=69), older adults (55 years to <65 years; n=92) and elders (≥65 years; n=139). Primary safety endpoints: implant survivorship and cumulative revision rate. Secondary endpoints: Knee Society Score (KSS), Western Ontario and McMaster universities osteoarthritis (WOMAC) score, range of motion (ROM), SF-36 questionnaire for assessment of quality of life (QoL), radiographic analysis, and any adverse events at 6 weeks, 6 months, 1-3 years. Results: Primary endpoint demonstrated absence of any revision across all age categories during the 3 years study period. Secondary outcomes KSS (clinical and functional) showed non-significant difference among elderly (91.13±7.90 and 98.18±4.62, respectively) in comparison to young adults (91.03±8.61 and 98.91±3.75, respectively). All three age-groups showed significant improvement in ROM (p<0.001) till 3 years 121.05°±7.74°, 123.22°±4.26°, and 122.43°±5.8° respectively, with no differences among the age groups. We observed that WOMAC and SF-36 QoL scores improved with each follow-up (p<0.001) across all age groups. Radiographs showed no implant wear or osteolysis during the investigation. Conclusions: Age seems to play no notable role on the post-TKA outcomes. Over a 3-year period, we observed marked enhancements in patient measures such as ROM, KSS, WOMAC, and QoL indicating and strongly affirming the safety and efficacy of CR/PS TKS prostheses.